Evaluating pavement condition using roadroid and Surface Distress Index (SDI): a case study of Klangon-Tempel Road, Yogyakarta Special Province - Ahmad, Fauji; Kushari, Berlian (Jurusan Teknik Sipil, Fakultas Teknik Sipil dan Perencanaan, Universitas Islam Indonesia, 2025)
Acquiring accurate condition out of pavement evaluation can prove to be a challenge, particularly for local road agencies in Indonesia with limited resources. Conventionally, road condition is expressed in terms of the Surface Distress Index (SDI) and the International Roughness Index (IRI) that need time-consuming and labor-intensive road surveys. Advancements in smartphone technology has paved the way to a lower-cost and more rapid pavement evaluation by using applications such as Roadroids for IRI measurements. This study is aimed at exploring the viability of Roadroids-based IRI for pavement evaluation purposes. Klangon-Tempel road section in Yogyakarta Special Province was selected as the study area, on which a manual SDI and two Roadroid-IRI surveys were conducted. The two Roadroid surveys involved two different vehicle types: a sport utility vehicle (SUV) and a multi-purpose vehicle. The results showed that MPV-survey produced higher IRI values and were more consistent with pavement distresses observed through SDI survey, demonstrating a strong correlation coefficient of r=0.813. In contrast, SUV-survey showed significantly lower IRI values that overestimate overall pavement condition of the study area. No detailed investigation was made, but MPV features such as lower ground clearance and softer suspension system may contribute to cause the different outcomes. Complementing this, a range-based SDI–IRI analysis showed that SDI and IRI are consistent at low-distress levels but display substantial overlap across medium-to-high SDI categories, reflecting their inherently non-linear relationship. The findings suggests that, with appropriate type of vehicle, Roadroid can be a viable choice to conduct rapid IRI-based pavement evaluation, and thereby complement the traditional SDI surveys.